The Representation of gender Ideology in Hinata Figure, Naruto Shippuden Film - Leni Tiwiyanti; Yulia Sofiani (Pusat Studi Pendidikan Bahasa dan Sastra Inggris, 2020)
Anime and manga can closely present Japanese culture. The concept of Hinata Hyuga as a woman ninja in Naruto Shippuden, an anime film, depicts the gender ideology of Japanese culture. The research aims to describe the representation of gender ideology in Hinata Hyuga's figure and to know the semiotic representation in Hinata Hyuga as a woman who has broken the Japanese gender ideology. The scope of this study is investigating the woman's identity in gender ideology (feminism), by seeing signs represented in Hinata Hyuga. The research is qualitative and applies a descriptive qualitative method. The primary data source of this research is taken from Naruto Shippuden animated film. After the animated film is obtained, the researchers watch several series which are related to Hinata Hyuga. To get the expected research purpose, theory by Simone de Beauvoir about gender ideology combined with semiotic Barthes is applied to analyze the representation of gender ideology. The results show that Hinata Hyuga is a Japanese woman who can be a strong ninja who has broken Japanese gender ideology. In short, by seeing signs, semiotic can prove that Hinata’s characterization is not defined as a weak woman. Hinata’s identity as a Japanese woman, who is expected to be calm, gentle, fragile and in charge of all the housework is deconstructed into a strong and brave woman who refuse to give up in any problems.